The Effects of Financial Inclusion and Financial Literacy on MSMEs' Financial Performance in Belitung - Amalia, Syafrina Nafla; Rosalina, Erita; Anggita, Wenni (LPPM STIE Krakatau, 2026)
ABSTRACT Purpose: The purpose of this study is to examine how financial inclusion and financial literacy affect MSMEs' financial performance in Belitung. Additionally, it aims to determine how each variable contributes to long-term gains in corporate performance. Methodology/approach: This study uses a survey method as part of a quantitative approach. A selective sample of 100 MSME operators in Belitung provided the data. A questionnaire based on measures of financial performance, financial inclusion, and financial literacy served as the research tool. Multiple linear regression analysis was then performed on the collected data using SPSS software. Results/findings: The study's findings show that financial literacy significantly and favourably affects MSMEs' financial performance in Belitung. In the meantime, it doesn't seem like financial inclusion significantly affects MSMEs' financial performance. Conclusions: These results suggest that enhancing MSME owners' financial success is mostly dependent on their capacity to comprehend and manage their finances. However, the ability to use formal financial services efficiently is a prerequisite for their direct influence. Limitations: The results of this study cannot yet be widely applied because it is restricted to a sample of 100 MSME operators in Belitung and only employs two independent variables. Contribution: This study offers empirical proof of the significance of financial inclusion and financial literacy in enhancing MSMEs' financial performance at the regional level. Keywords: financial literacy; financial inclusion; financial performance; MSMEs